Imperceptible manipulation of lateral camera motion for improved virtual reality applications - Serrano, Ana; Martin , Daniel; Gutierrez, Diego; Myszkowski, Karol; Masia, Belen (Jornada de Jóvenes Investigadores del I3A, 2020)
We measure detection thresholds for lateral translation gains of virtual camera motion in response to the corresponding head motion under natural viewing. We propose three applications for our method, addressing three key problems in virtual reality, and validate their improvement when our manipulation technique is applied.